1993
DOI: 10.1111/j.1365-2125.1993.tb05680.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an oral dose of isosorbide dinitrate on platelet function and fibrinolysis in healthy volunteers.

Abstract: 1. A randomised double‐blind placebo‐controlled study was performed to investigate the effects of isosorbide dinitrate (ISDN; 20 mg orally) on various aspects of platelet function and fibrinolysis in vivo in 12 healthy volunteers. 2. Measurements were performed at rest (before and after tablet ingestion) and during platelet activation by adrenaline (0.4 nmol kg‐1 min‐1; 30 min infusion). 3. At rest, ISDN did not alter plasma concentrations of beta‐thromboglobulin (beta TG). EC50 values for ADP induced aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
8
2
Order By: Relevance
“…In contrast to our findings in healthy volunteers [12], there were no relationships between ISDN induced vasodilation (i.e. the decrease in systolic blood pressure at rest, calculated as placebo values minus ISDN values) and the filtragometry readings-either at rest or during platelet activation by exercise (the platelet activating effect was expressed either as the percent decrease in tA (exercise divided by rest), or the corresponding algebraic difference (i.e.…”
Section: Filtragometry Measurements (Figure 2)contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings in healthy volunteers [12], there were no relationships between ISDN induced vasodilation (i.e. the decrease in systolic blood pressure at rest, calculated as placebo values minus ISDN values) and the filtragometry readings-either at rest or during platelet activation by exercise (the platelet activating effect was expressed either as the percent decrease in tA (exercise divided by rest), or the corresponding algebraic difference (i.e.…”
Section: Filtragometry Measurements (Figure 2)contrasting
confidence: 99%
“…On the other hand, platelet function is complex and platelet attenuating effects of nitrates may not be revealed with insensitive in vitro techniques or when measurements are performed only at rest. In healthy volunteers ISDN tended to attenuate platelet responses in vivo to adrenaline infusion, without any effect in the basal state [12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…14,32,33 Recent observations are that fibrinolysis with tPA activity, tPA antigen and PAI-1 activity depend on catecholamine levels. 24,[34][35][36][37] A previous report suggested that non-selective -blockers abolished fibrinolytic activity mediated by epinephrine. 38 Our results show that SNA is significantly related to PAI-1 activity during LBNP, which suggests that PAI-1 activity would be increased by enhanced sympathetic efferent neuronal activity.…”
Section: Discussionmentioning
confidence: 99%
“…LBNP is well known to increase SNA and catecholamine concentration by reducing baroreceptor restraint. 41,42 Previous results suggest that dose-dependent stimulation with an infusion of epinephrine increases PAI-1 activity within 15-40 min, 35 which suggests that elevation of catecholamine levels or orthostatic stress induces a hypercoagulable state. However, the measurement of catecholamine levels is largely influenced by factors such as posture and mental stress, so we evaluated direct recording of efferent SNA, which enables an exact response of SNA to be measured during physiological stress.…”
Section: Discussionmentioning
confidence: 99%